Length weight relationship and condition factor of Australian red claw crayfish (Cherax quadricarinatus) from three locations in Peninsular Malaysia - Syed Idrus, Syed Naguib; Sallehuddin, Ahmad Safuan; Kamarudin, Ahmad Syazni; Mohd Dali, Mohamad Zulkarnain; Kassim, Zaleha; Lokman, Mohd Ilham Norhakim; Ismail, Norshida (Innovative Scientific Information & Services Network, 2021)
Australian redclaw crayfish, Cherax quadricarinatus, is a species of crayfish native to northern Australia and southern New Guinea but has been introduced and established feral population in many parts of the world including in Malaysia. In this present study, we examined some morphometric characteristics of C. quadricarinatus collected from three locations in Malaysia which are Tasik Ayer Keroh (Melaka), Muar (Johor) and Besut (Terengganu). The wild-caught crayfishes found in these selected locations were analyzed for sex ratio, length-weight relationships (LWRs) and condition factor (K). The sex ratio of C. quadricarinatus from Melaka, Johor and Terengganu was found to be 0.73:1 (19 females/26 males), 2.9:1 (26 females/9 males) and 0.28:1 (4 females/14 males) respectively. The LWRs for redclaw crayfish from Melaka, Johor and Terengganu were W = 0.018L3.06, W = 0.011L3.19, and W = 0.016L3.08, respectively. C. quadricarinatus from the three locations show positive allometric growth (b>3). The K values for Melaka, Johor and Terengganu were 2.07, 1.76 and 1.84 respectively. The findings show that redclaw populations from different localities in Peninsular Malaysia attained good condition and this might reflect that the species has adapted well in our environment.